2020
DOI: 10.1007/s40940-020-00135-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel concept for a reinforced glass beam carrying long term loads

Abstract: This paper presents a novel concept for improving the long-term load-bearing performance of reinforced glass beams (hybrid beams). The concept of reinforcing glass beams using steel or other (ductile) materials have been investigated over the last couple of decades utilising the fracture pattern of annealed glass to ensure a ductile behaviour. However, it is well known that the long-term strength of annealed glass is rather low due to so-called static fatigue leading to a relatively poor performance for most h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Structurally speaking, typical manifestations of a possible mechanical capacity loss due to long-term effects are possibly associated with the progressive material deterioration and/or delamination of the constituent layers, which further involves a reduction of load-bearing capacity [ 25 ] with similar criticalities to laminated glass members [ 26 , 27 ]. This is especially the case for long-term mechanical loads or unfavourable temperatures [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Structurally speaking, typical manifestations of a possible mechanical capacity loss due to long-term effects are possibly associated with the progressive material deterioration and/or delamination of the constituent layers, which further involves a reduction of load-bearing capacity [ 25 ] with similar criticalities to laminated glass members [ 26 , 27 ]. This is especially the case for long-term mechanical loads or unfavourable temperatures [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in architectural glazing, the use of heat-strengthened and/or fully tempered glass is standard, due to its higher strength. Some case studies and examples utilising heatstrengthened or fully tempered glass can be found in [1][2][3][4][5]. Fully tempered glass is also known as safety glass due to its complete fragmentation into small dices upon failure also known as frangibility, see e.g.…”
Section: Introductionmentioning
confidence: 99%